New architectural and planning solutions as a mean of ecological modernization and reconstruction of urban environment (on the example of Shanghai city, China). (November 2019) - Van, Shanshan; Cheremisin, Alexey; Chusov, Alexander; Zueva, Olga; Dolgopolov, Alexey; Nikulina, Elena; Switala, Franciszek; Davydov, Roman
Abstract: The results of research represented in the article relate to ecological modernization and reconstruction of urban environment on the example of planning efficient usage and improvement of former industrial zones territories of Shanghai city. A one of them is Taopu district. The main criteria and content of environmental assessment are developed. The territories were redeveloped with taking into account environmental potential of the urban areas on the base of calculations carried out and analysis of data obtained. Planning for further use of the former Taopu industrial zone could help the theory and practical experience of construction of eco-cities in China and in the world.